Effect of Fungicides on Colony Growth of Colletotrichum Lindemuthianum (Sacc. & Magn.) Scrib - Sartori, Juliana Elisa [UNESP]; Maringoni, Antonio Carlos [UNESP] (Polish Academy of Sciences Chancellery, 2008)
Colletotrichum lindemuthianum (Sacc. & Magn.) Scrib. is the causal agent of the anthracnose of common bean (Phaseolus vulgaris L.), a fungal disease of a great significance in brazilian bean cultures. The goals of this work were to evaluate the in vitro colony growth and to determine the ED50 interval of twenty C. lindemuthianum isolates from different regions of Brazil to five fungicides of different active ingredients and to some blendings (carbendazim, chlorothalonil, thiophanate-methyl, chlorothalonil + thiophanate-methyl, trifloxystrobin, propiconazole and trifloxystrobin + propiconazole), at concentrations of 0, 1, 10, 100 and 1 000 µg/ml, in a potato-dextrose-agar culture medium. The results revealed seven isolates with low sensitivity to carbendazim and thiophanate-methyl (ED50 interval greater than 1000 µg/ml) thus suggesting cross-resistance. Isolate sensitivity to chlorothalonil ranged from ED50 interval less than 1 µg/ml to greater than 1 000 µg/ml. Those isolates with high sensitivity to thiophanate-methyl, ED50 interval less than 1 µg/ml, did also show it with respect to chlorothalonil + thiophanate-methyl. Sixteen isolates showed a high sensitivity to trifloxystrobin with a ED50 interval less than 1 µg/ml. Nineteen isolates of C. lindemuthianum showed high sensitivity to propiconazole and to trifloxystrobin + propiconazole with ED50 interval less than 1 µg/ml. Isolates with low sensitivity to carbendazim and thiophanate-methyl were sensitive to propiconazole and to trifloxystrobin + propiconazole. Variability was found in the sensitivity of the colony growth of C. lindemuthianum isolates from different regions of Brazil to the fungicides evaluated. © 2008, Versita. All rights reserved.
Keywords: anthracnose of common bean; Colletotrichum lindemuthianum; fungicide; Phaseolus vulgaris